Building mountain biodiversity: Geological and evolutionary processes - Rahbek, Carsten; Borregaard, Michael K.; Antonelli, Alexandre; Colwell, Robert K.; Holt, Ben G.; Nogues-Bravo, David; Rasmussen, Christian M. Ø.; Richardson, Katherine; Rosing, Minik T.; Whittaker, Robert J.; Fjeldså, Jon (Science (American Association for the Advancement of Science), 2019)
Mountain regions are unusually biodiverse, with rich aggregations of small-ranged species that form centers of endemism. Mountains play an array of roles for Earth’s biodiversity and affect neighboring lowlands through biotic interchange, changes in regional climate, and nutrient runoff. The high biodiversity of certain mountains reflects the interplay of multiple evolutionary mechanisms: enhanced speciation rates with distinct opportunities for coexistence and persistence of lineages, shaped by long-term climatic changes interacting with topographically dynamic landscapes. High diversity in most tropical mountains is tightly linked to bedrock geology—notably, areas comprising mafic and ultramafic lithologies, rock types rich in magnesium and poor in phosphate that present special requirements for plant physiology. Mountain biodiversity bears the signature of deep-time evolutionary and ecological processes, a history well worth preserving.